2014
DOI: 10.1021/bm500733h
|View full text |Cite
|
Sign up to set email alerts
|

A Tail of Two Peptide Amphiphiles: Effect of Conjugation with Hydrophobic Polymer on Folding of Peptide Sequences

Abstract: Peptide amphiphiles (PA) offer the potential of incorporating biological function into synthetic materials for tissue engineering in regenerative medicine. These hybrid conjugates are known to undergo self-assembly starting from single molecules to nanofibers before turning into hydrogel scaffolds-such a process involves conformational changes in secondary structures of peptides. Therefore, insights on the ability of peptide amphiphiles to form secondary structure as single molecules are useful for understandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In addition, we have performed a more detailed study previously on peptide folding by PA1 and PA2 using the atomistic CHARMM model. The alkyl tail was observed to play two opposing roles in modulating sequence-dependent folding kinetics and thermodynamics. On one hand, it restricts conformational freedom reducing the entropic cost of folding, which is thus promoted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have performed a more detailed study previously on peptide folding by PA1 and PA2 using the atomistic CHARMM model. The alkyl tail was observed to play two opposing roles in modulating sequence-dependent folding kinetics and thermodynamics. On one hand, it restricts conformational freedom reducing the entropic cost of folding, which is thus promoted.…”
Section: Resultsmentioning
confidence: 99%
“…While the use of reduced quantities in silico poses difficulty in achieving an experimental analogue, qualitative correlations can be extracted. From earlier work examining single-molecule behavior using both atomistic and coarse-grained models, , a qualitative frame of reference can be identified correlating the melting temperature of T * = 0.085 to T ∼ 320 K.…”
Section: Methodsmentioning
confidence: 99%
“…Such a reweighting can be done with the weighted histogram analysis method (WHAM) , or the multistate Bennet acceptance ratio (MBAR) method. , We used the MBAR method implemented in the Pymbar software to reweight the conformational ensembles related to each replica. From the overall conformational ensemble, a two-dimensional potential of mean force (2D-PMF) was computed using the Pymbar software and Q loop interactions and Q binding site as reaction coordinates, yielding a relative free energy Δ G for every bin of the 2D-PMF. The uncertainties for the calculated 2D-PMFs were estimated with the Pymbar software . We performed a worst-case estimation for the errors, for which only uncorrelated snapshots from the trajectories were considered.…”
Section: Methodsmentioning
confidence: 99%
“…Polymers that interact with hydrophobic residues can kinetically disrupt folding pathways by blocking nucleating sites. 17 Coarse-grained (CG) simulations of model peptides found that glycosylation at flexible residues increases conformational stability and facilitates folding, whereas glycosylation at highly structured residues increases the folding free energy barrier and can significantly hinder folding. 18,19 Advances in computer architectures and simulations methods are allowing a deeper understanding of many of these more nuanced conjugation effects on folding and assembly, beyond excluded volume, as recently reviewed by Lee.…”
Section: Introductionmentioning
confidence: 99%